Echinatin mitigates sevoflurane-induced hippocampal neurotoxicity and cognitive deficits through mitigation of iron overload and oxidative stress - Zilong Xu; Yanqiu You; Qiuqin Tang; Hui Zeng; Tianshou Zhao; Juan Wang; Fujun Li (Taylor & Francis Group, 2022)
Context Sevoflurane (Sev) is a commonly used surgical anaesthetic; it has neurotoxic effects on the brain. Echinatin (Ech) is reported to have anti-inflammatory and antioxidant activity.Objective This research confirms the effect of Ech on Sev-induced neurotoxicity and cognitive deficits.Materials and methods Primary rat hippocampal neurons were treated with 4.1% Sev for 6 h in the presence of Ech (5, 10, and 20 μM) or vehicle, followed by a further 42 h of culture. Male Sprague-Dawley aged rats were divided into 6 groups (n = 6): control, Sev, Sev + Ech (20 mg/kg;), Sev + Ech (40 mg/kg), and Sev + Ech (80 mg/kg). Rats were intraperitoneally injected with Ech or vehicle 1 h before Sev exposure (2% Sev for 5 h).Results We found that Ech (5, 10, and 20 μM) elevated cell viability (1.29-, 1.51-, 1.68-fold) but mitigated apoptosis (23.87% vs. 16.48%, 12.72%, 9.02%), oxidative stress, and ferroptosis in hippocampal neurons with Sev treatment. Ech activated the Nrf2 expression in Sev-induced in vitro and in vivo models of anaesthetic neurotoxicity. Ech also weakened neurotoxicity in hippocampal neurons with Sev treatment by increasing Nrf2 expression level. Moreover, Ech alleviated hippocampus neurons apoptosis (19.38% vs. 16.05%, 11.71%, 8.88%), oxidative stress, and ferroptosis in rats with Sev treatment. Ech improved Sev-induced cognitive deficits in rats.Conclusions Ech alleviates Sev-induced neurotoxicity and cognitive deficits by mitigation of ferroptosis and oxidative stress. Ech may be developed as a new promising therapeutic drug for treatment of cerebral nerve injury caused by surgical anaesthesia.